Analisis Auditor switching Secara Voluntary yang dipengaruhi oleh Opini Audit, Pergantian Manajemen, Financial Distress, Audit Delay pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2015-2017 - Yanto Yanto; Sri Wahyuni Almunawaroh (Accounting Study Program, Faculty of Economics and Business, 2019)
This study aims to examine the effect of audit opinion, management turnover, financial distress, and audit delay on voluntary auditor switching in manufacturing companies. Several previous studies on the factors that influence voluntary auditor switching still show different results. Therefore, it is necessary to re-examine the factors that influence voluntary auditor switching. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017 as many as 144 companies. Based on the purposive sampling method, the research sample consisted of 129 manufacturing companies for the 2015-2017 period. The data used in this research is secondary data. The analytical tool used to test the hypothesis in this study is logistic regression analysis with SPSS 23 program and a significance level of 5%. The results of hypothesis testing indicate that there is evidence that all independent variables, namely audit opinion, management turnover, financial distress, and audit delay have no significant effect on voluntary auditor switching.